Arbitragem e corrupção: o dever de denúncia pelo árbitro - Marçal, Juliana Ferreira da Silva (2021)
The purpose of this paper is to present a critical analysis of the arbitrator's possible duty to notify the Public Prosecutor if there is evidence that the contract under review in the arbitration proceeding may result from corruption. For this purpose, were examined the confidentiality of the arbitration proceeding, the arbitrability of disputes involving corruption, the legislation applicable to acts of corruption and its legal consequences, the burden of proof involving corruption allegations. In addition, through the analysis of decisions rendered by international arbitral tribunals, the position adopted by these institutions was identified and it was possible to obtain a broader dimension of the issue